2019
DOI: 10.1038/s41416-019-0665-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of human primary breast cancer identifies fatty acid oxidation as a target for metformin

Abstract: BACKGROUND: Epidemiological studies suggest that metformin may reduce the incidence of cancer in patients with diabetes and multiple late phase clinical trials assessing the potential of repurposing this drug are underway. Transcriptomic profiling of tumour samples is an excellent tool to understand drug bioactivity, identify candidate biomarkers and assess for mechanisms of resistance to therapy. METHODS: Thirty-six patients with untreated primary breast cancer were recruited to a window study and transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…Therefore, the inhibition of PKM2 causes calcium overload and cell death, rather than the expected metabolic catastrophe. In a different context, breast cancer, Lord and colleagues 14 elegantly showed that metformin, a drug commonly used in Type 2 diabetes but with promising yet unclear anticancer effects, acts as an inhibitor of fatty acid oxidation at clinical doses. This work, together with their previous finding that the mitochondrial response to metformin in primary breast cancer defines antitumour effect, 15 suggests that metabolic profiling can be used to predict the response to metformin, and more in general to anticancer drugs.…”
Section: Targeting Metabolismmentioning
confidence: 99%
“…Therefore, the inhibition of PKM2 causes calcium overload and cell death, rather than the expected metabolic catastrophe. In a different context, breast cancer, Lord and colleagues 14 elegantly showed that metformin, a drug commonly used in Type 2 diabetes but with promising yet unclear anticancer effects, acts as an inhibitor of fatty acid oxidation at clinical doses. This work, together with their previous finding that the mitochondrial response to metformin in primary breast cancer defines antitumour effect, 15 suggests that metabolic profiling can be used to predict the response to metformin, and more in general to anticancer drugs.…”
Section: Targeting Metabolismmentioning
confidence: 99%
“…12 Met represses fatty acid oxidation independent of AMP kinase (AMPK) activation, which results in an accumulation of intracellular triglycerides in breast cancer cells. 13 Nonetheless, the anticancer mechanism of Met remains unclear. In the present study, we examined whether, in addition to cancer cells, Met can be used to target the breast cancer TME to render it inhospitable for cell growth and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…However, since many metabolic pathways in cancer cells are far different from those in non-malignant cells, caution should be taken to extrapolate the linkage between modulation of tumor growth and FAO by adiponectin. In fact, metformin, a potent activator of AMPK and FAO under physiological conditions, was demonstrated to inhibit FAO in breast cancer cells [ 105 ]. In summary, although adiponectin possesses various effects on lipid metabolism, future investigations are required for unraveling the involvement of adiponectin-induced alterations in cancer-related lipid metabolism in tumor progression.…”
Section: Effects Of Adipokines On Cancer Metabolismmentioning
confidence: 99%
“…It has been suggested that AMPK activators, such as AICAR (5-aminoimidazole-4-carboxamide-1-β-d-ribofuranoside) and metformin, show metabolic effects similar to adiponectin under physiological conditions [ 168 , 169 , 170 ]. Furthermore, compelling evidence indicates that AMPK activators suppress tumor growth though inhibition of de novo lipogenesis [ 105 , 171 , 172 ]. Therefore, reactivation of AMPK may serve as a potential intervention to reverse promoting effects of obesity on cancer metabolism.…”
Section: Targeting Adipokines-driven Cancer Metabolism For Countermentioning
confidence: 99%